Development of a structural equation model of resilience based on cognitive flexibility and cognitive emotion regulation: The mediating role of intimacy and marital adjustment among nurses - Mohsen Kamalinia; Kianoush Zahrakar; Mehdi Arabzadeh (روانشناسی و روانپزشکی شناخت)
Introduction: Resilience is a key psychological construct that plays a crucial role in coping with workplace challenges and marital stress. Given its significance, identifying factors that predict resilience is essential for enhancing well-being in both professional and personal domains. Aim: This study aimed to develop a resilience model based on cognitive flexibility and self-differentiation, with intimacy and marital adjustment as mediating variables. Method: The present study employed a quantitative, descriptive-correlational design. The sample consisted of married female nurses working in health centers and government hospitals in Karaj city during 2022, selected from a population of 2,938 nurses (400 participants) through multi-stage cluster sampling. Data were collected using the Connor-Davidson Resilience Scale, Dennis and Vanderwaal’s Cognitive Flexibility Scale, Granofsky's Cognitive Emotion Regulation Questionnaire, Bagarozi’s Marital Intimacy Scale, and the Locke-Wallace Marital Adjustment Scale. The data were analyzed using SPSS version 24 and AMOS version 26. Results: The indirect path coefficient between cognitive flexibility and resilience through marital intimacy (0.248) was found to be significant. Similarly, the indirect path coefficient between cognitive emotion regulation and resilience through marital intimacy (0.352) was significant. The indirect path coefficient between cognitive flexibility and resilience through marital adjustment (1.899) was also significant. Furthermore, the indirect path coefficient between Heechan's cognitive regulation and resilience through marital adjustment (0.202) was significant. Conclusion: Increasing cognitive flexibility and cognitive emotion regulation positively influences resilience. Therefore, it is recommended to prioritize the cognitive, emotional, and affective variables in interventions for this group.